2022
DOI: 10.7759/cureus.25467
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Aspirin, Promethazine, and Micronutrients for Rapid Clinical Recovery in Mild to Moderate COVID-19 Patients: A Randomized Controlled Clinical Trial

Abstract: can offer speedy clinical recovery to reduce the burden on healthcare infrastructure, second, the combination shows significant anti-inflammatory potential to improve prognosis, and lastly, the immunomodulatory properties offer long-term protection that can help in combating long COVID symptoms and complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Promethazine, an antipsychotic agent showing clathrin-mediated endocytosis, is one most effective drugs for SARS-CoV and MERS-CoV, which has been repurposed for the treatment of COVID-19 as there is almost 89% genetic similarity with SARS-CoV-2 and SARS-CoV [ 131 ]. Two pills were offered as an intervention, one with Aspirin and Promethazine and the other with vitamins D3, C, and B3, together with Zinc and selenium supplements [ 132 ]. A randomized clinical trial has been conducted to recover mildly to moderate COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Promethazine, an antipsychotic agent showing clathrin-mediated endocytosis, is one most effective drugs for SARS-CoV and MERS-CoV, which has been repurposed for the treatment of COVID-19 as there is almost 89% genetic similarity with SARS-CoV-2 and SARS-CoV [ 131 ]. Two pills were offered as an intervention, one with Aspirin and Promethazine and the other with vitamins D3, C, and B3, together with Zinc and selenium supplements [ 132 ]. A randomized clinical trial has been conducted to recover mildly to moderate COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this validation, further research on the repurposed drug, docking study, and other symptomatic analyses will help to identify the potential drug for the entire coronavirus family. A clinical study on Promethazine and Fostamatinib [ 115 , 132 ] is also in progress. Even though the research is in its early stages, it in some way partially corroborates our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports, however, demonstrated that knocking out the clathrin heavy chain blocked CME and reduced SARS-CoV-2 infectivity [ 87 , 108 ]. In addition, Promethazine was suggested based on its ability to inhibit clathrin, and to reduce the symptoms and inflammation associated with SARS-CoV-2 infection [ 109 ]. Chlorpromazine, bolinaquinone (clathrin inhibitor), and Pitstop 2 are known to prevent the scission of the CCVs from the plasma membrane [ 110 ].…”
Section: Sorting Endocytic Proteins and Lipids As Anti-sars-cov-2 Tar...mentioning
confidence: 99%
“…Faster recovery was seen in participants from the treatment group, as demonstrated by significantly reduced levels of CRP, LDH, and ferritin. This study has provided preliminary evidence for further analysis of micronutrients, such as vitamins and minerals, as well as aspirin in the management of COVID-19 [ 26 ].…”
Section: Reviewmentioning
confidence: 99%
“…Assessments at baseline and on Days 5 and 10 have implied significant improvement of symptoms and inflammatory marker levels in hospitalized patients. Therefore, APVM2020 is a good candidate to be included in the COVID-19 management protocol [ 26 ].…”
Section: Reviewmentioning
confidence: 99%